2014
DOI: 10.1538/expanim.63.277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Behavioral Performanceof Streptozotocin-induced Diabetic Mice inAnxiety Tests

Abstract: The aim of this study was to evaluate with anxiety tests the effect of resveratrol (RSV) on streptozotocin (STZ)-induced diabetic mouse behavioral performance at the second and fourth week of treatment. Confirmed diabetic mice (>250 mg/dl of glucose in blood after STZ injection) were treated with RSV (RDM, n=12) or control treated (DM, n=12) for 4 weeks. DM and RDM were tested in the Open Field Test (OFT) and Elevated Plus Maze (EPM). In the second week of RSV treatment, a higher grooming frequency (P<0.05) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 82 publications
1
21
0
Order By: Relevance
“…In line with the results of these studies, our results showed that aging and ovariectomy (bilateral ovarian ablation) increases the expression of anxiety behaviors. Furthurmore, other studies have shown that the use of antioxidants can reduce anxiety behaviors in humans and animals . The antioxidant activity of Met has been shown in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of these studies, our results showed that aging and ovariectomy (bilateral ovarian ablation) increases the expression of anxiety behaviors. Furthurmore, other studies have shown that the use of antioxidants can reduce anxiety behaviors in humans and animals . The antioxidant activity of Met has been shown in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Natural flavonoids have been effective in reversal of anxiety-like behavior in diabetic mice has been detected in EPM test (Damian et al, 2014, Tang et al, 2015. Insulin plays a critical role in hippocampal memory processing and hyperglycemia is responsible for cognitive deficit and neuronal damage following DM (Abbatecola et al, 2006, Strachan et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The open-field test is a behavioral test to evaluate anxiety-like behavior based on the locomotor activity (Damián et al, 2014[22]; Motaghinejad et al, 2016[47]). The open-field apparatus consists of a plexiglass square box with walls to reduce outside noise and light.…”
Section: Methodsmentioning
confidence: 99%